Collaborative Strategy of Ministry of Defense and BNPT in Counterterrorism Efforts to Strengthen National Security - Nooryadi, Irfan Fahmi; Dohamid, Ahmad G; Prihartoro, Mitro (CV. Rayyan Dwi Bharata, 2025)
Terrorism is one of the primary threats to Indonesia's national security, involving ideological, social, political, and economic aspects. The complexity of this threat necessitates a comprehensive approach involving various institutions, including the Ministry of Defense (Kemhan) and the National Counter-Terrorism Agency (BNPT). This study aims to analyze the collaborative strategies between Kemhan and BNPT in counterterrorism efforts and evaluate their impact on strengthening national security. Using a qualitative research method and literature review as the primary approach, data were analyzed through content analysis to identify collaboration patterns and challenges. The findings indicate that the collaboration between Kemhan and BNPT is implemented through joint policy formulation, integrated operations, intelligence strengthening, and community empowerment. While this collaboration has positively contributed to threat prevention, effective action, and social resilience, challenges such as overlapping authority and resource limitations remain obstacles. The study concludes that a more structured and technology-based collaborative strategy is required to enhance counterterrorism effectiveness. Recommendations include improving institutional coordination, developing cross-sectoral policies, and strengthening resources. This study is expected to serve as an academic and practical reference for formulating counterterrorism strategies in Indonesia.